PC.15 The UK Neonatal Collaborative Necrotising Enterocolitis (NEC) Study: development of an evidence-based case-definition for NEC. (9th June 2014) - Battersby, C; Santhakumaran, S; Costeloe, K; Modi, N
Abstract : Objective: Lack of a universal case-definition hinders (NEC) surveillance and clinical trials. Bell's staging, although widely used, was devised to guide surgical management after diagnosis 1 . We aimed to develop an evidence-based NEC case-definition. Methods: We used the National Neonatal Research Database, that holds data extracted from the electronic records of babies admitted to NHS neonatal units, to obtain variables for infants receiving a laparotomy between November 2011–May 2013 (gestation, clinical signs (abdominal distension, tenderness, discolouration, mass, increased and/or bilious aspirates, bloody and/or mucousy stools), radiological signs (pneumatosis, air in the liver, pneumoperitoneum, fixed loop, gasless), confirmed NEC (at surgery or post-mortem). We developed case-definitions using logistic regression and classification trees 2, and calculated sensitivity, specificity and area under the receiver operating characteristic curve (AUC). Interim validation was conducted using a separate dataset covering June–December 2013. Results: We identified 142 infants from 40 neonatal units; 60 had confirmed NEC. The logistic regression definition comprised "pneumatosis OR two or more of (a) abdominal discolouration, (b) gasless X-ray (c) pneumoperitoneum" (sensitivity 0.72, specificity 0.88, AUC 0.8) and classification tree definition "pneumatosis OR abdominal discolouration OR [pneumoperitoneum AND aspirates]" (sensitivity 0.85, specificity 0.78, AUC 0.82). Validation showed logistic regression: sensitivity 0.64, specificity 0.95, AUC 0.85; classification tree sensitivity 0.67, specificity 0.91, AUC 0.79. Conclusion: Our interim analysis shows that the two methods derived similar definitions identifying a similar proportion of cases; pneumatosis was the strongest predictor. The final analysis will include data from June 2013-April 2014 and will investigate gestation-specific effects. References: Bell MJ, Ternberg JL, Feigin RD, et al . Neonatal necrotizing enterocolitis. Therapeutic decisions based upon clinical staging. Ann Surg . 1978;187:1–7 Online First: 1978/01/01] Crichton NJ, Hinde JP, Marchini J. Models for diagnosing chest pain: is CART helpful? Stat Med. 1997;16:717–27 Online